Piperine-hydroxy acid-cyclodextrin inclusion complexes; antioxidant, antiinflammatory, and stability studies: PART II - Jadhav, Priyanka (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Piperine (PIP) is a natural ingredient possessing important biological activities. However, its practical usefulness is limited due to its low water solubility. In our previous research article (PART A), we demonstrated inclusion complexation of PIP with cyclodextrins (CDs) in the influence of certain hydroxy acids resulted in tremendous improvement in physicochemical characteristics of PIP. The aim of current research work was to study biological properties and stability analysis of PIP and its lyophilized inclusion complexes. Materials and Methods: Initially, Job’s plot experiment was carried out to assess the type of solubility and stoichiometry of complexes. The solid inclusion complexes were obtained by lyophilization and characterized by differential scanning calorimetry (DSC), X-ray powder diffractometry (XRPD), saturation solubility, in-vitro dissolution, in-vitro antioxidant activity, and in-vivo anti-inflammatory activity in carrageenan-induced rat paw edema model. The short-term stability studies were carried out as per the ICH guidelines. Results: During assessment, the complexes performed better in terms of in-vitro antioxidant and in-vivo anti-inflammatory activities than the native PIP. However, PIP: Hydroxypropyl β-CD (HPβCD): Ascorbic acid (AA) ternary complexes elicited immediate and maximum onset of anti-inflammatory action, as compared to other test samples. In the stability studies, no noteworthy changes were recorded concerning DSC, XRPD, and in-vitro dissolution studies over a period of 6 months except complexes with HPβCD. Conclusion: Taking everything into account, complexation of PIP with CDs, in the influence of AA, would be a successful way to improve its biological properties.